Colorectal Cancer Screening: A Comprehensive Review to Recent Non-Invasive Methods - Hamzehzadeh, Leila (Int J Hematol Oncol Stem Cell Res, 2017)
Colorectal cancer (CRC) is one of the most common cancers worldwide and considered to be one of the hassles in medical communities. CRC develops from precancerous polyps in the colon or rectum and is preventable and curable by an early diagnosis and with the removal of premalignant polyps. In recent years, scientists have looked for inexpensive and safe ways to detect CRC in its earliest stages. Strong evidence shows that screening for CRC is a crucial way to reduce the incidence and mortality of this devastating disease. The main purpose for screening is to detect cancer or pre-cancer signs in all asymptomatic patients. In this review, we holistically introduce major pathways involved in the initiation and progression of colorectal tumorgenesis, which mainly includes chromosome instability (CIN), microsatellite instability (MSI), the CpG island methylator phenotype (CIMP), and we then will discuss different screening tests and especially the latest non-invasive fecal screening test kits for the detection of CRC.